INDONESIA’S MIGRANT WORKERS AND OVERSEAS LABOR POLICY - Tirtosudarmo, Riwanto; Mulyani, Lilis (P2KK LIPI, 2013)
Demographically, Indonesia is the fourth largest country in the world, yet international migration is a meager issues and only recently becoming a hot policy debates on the problem of migrant workers protection. The huge demand for domestic workers since the mid 1980s from the Gulf countries, Malaysia, Singapore and Hong Kong, continue unabated, increasingly creates tensions between the state and the civil societies, as many migrant workers exposed to exploitation and human right abuses. The center of the tension lays on the wide discrepancy between the policy to bolster the overseas labor and the failure of the state in providing a proper regulation in which protection for migrant workers is secured. To understand the current problems of overseas labor policy in Indonesia is necessary to trace the relationship between migration and the state and the history of state policy on migration. Assessing the role of stakeholders in this migration industry is important in able to understand the apparently lack of grasp and continuously reactionary and ad hock nature of the policy and related regulations. Keywords: Indonesia’s overseas labor policies, migrant workers, migration of labor